Transcriptome Analysis of Endogenous Hormone Response Mechanism in Roots of Styrax tonkinensis Under Waterlogging - Chen, Hong; Wu, Qikui; Ni, Ming; Chen, Chen; Han, Chao; Yu, Fangyuan (Frontiers in Plant Science, 2022)
As a promising oil species, Styrax tonkinensis has great potential as biofuel due to excellent fatty acid composition. However, frequent flooding caused by global warming and the low tolerance of the species to waterlogging largely halted its expansion in waterlogged areas. To explore endogenous hormones and phytohormones-related molecular response mechanism of S. tonkinensis under waterlogging, we determined 1-aminocyclopropane-1-carboxylic acid (ACC) and three phytohormones content (abscisic acid: ABA, salicylic acid: SA and indole-3-acetic acid: IAA), and analyzed transcriptome of its seedlings under the waterlogged condition of 3-5 cm. The sample collecting time was 0h, 9h, 24h and 72h, respectively. It was concluded that ACC presented an upward trend, but other plant hormones showed a downward trend from the 0h to 72h under waterlogging stress. A total of 84,601 unigenes were spliced with a total length of 81,389,823 bp through transcriptome analysis. The GO enrichment analysis of total differentially expressed genes (DEGs) revealed that 4,637 DEGs, 8,238 DEGs, and 7,146 DEGs were assigned into three main GO functional categories in 9h vs 0h, 24h vs 0h, and 72h vs 0h, respectively. We also discovered several DEGs involved in phytohormones synthesis pathway and plant hormone signaling pathway. It was concluded that the decreased transcription of PYL resulted in the weak ABA signal transduction pathway. Moreover, decreased SA content caused by the low-expressed PAL reduced the resistance of S. tonkinensis seedlings under waterlogging stress. Our research may provide a scientific basis for the understanding of the endogenous hormone response mechanism of S. tonkinensis to waterlogging and lay a foundation for further exploration of the waterlogging defect resistance genes of S. tonkinensis and improving its resistance to waterlogging stress.